Benin : First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of Performance Criterion, Request for Program Extension and Rephasing of Performance Criteria - Staff Report; Press Release; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report, 2011)
Performance under the Extended Credit Facility (ECF) program has been mixed. The revenue slippage was addressed partially with corrective actions. IMF staff supports the authorities' request for a waiver of a missed performance criterion and recommends the completion of the first review. The collapse of a number of unauthorized microfinance institutions has not had a measurable impact on the financial sector. Ex post assessment of performance under the 2005-09 poverty reduction and growth facility program highlighted progress in macroeconomic stabilization but weaknesses in growth performance.